Combining biological therapies in patients with inflammatory bowel disease: a Finnish multi-centre study. (3rd August 2022) - Eronen, Heli; Kolehmainen, Sara; Koffert, Jukka; Koskinen, Inka; Oksanen, Pia; Jussila, Airi; Huhtala, Heini; Sipponen, Taina; Ilus, Tuire
Abstract: Background and aims: Therapy with two concomitant biologicals targeting different inflammatory pathways has emerged as a new therapy option for treatment refractory inflammatory bowel disease (IBD). Data on the efficacy and safety of dual biological therapy (DBT) are scarce and are investigated in this study. Materials and methods: Data on all patients treated with a combination of two biologicals in four Finnish tertiary centres were collected and analysed. Remission was assessed by a physician on the basis of biomarkers, endoscopic evaluation and alleviation of symptoms. Results: A total of 16 patients with 22 trials of DBT were included. Fifteen patients had Crohn's disease. The most common combination of DBT was adalimumab (ADA) and ustekinumab (USTE; 36%) with median follow-up of nine months (range 2–31). Altogether seven (32%) patients were in remission at the end of follow-up and in two trials response to DBT was assessed to be partial with the relief of patient symptoms. In a total of four trials DBT reduced the need for corticosteroids. The majority of patients achieving a response to DBT were treated with the combination of ADA and USTE (56%). At the end of follow-up all nine (41%) patients responding to DBT continued treatment. Infection complications occurred in three patients (19%). Conclusion: DBT is a promising alternative treatment for refractory IBD, and half of our patients benefitted from it. More data on the efficacy and safety of DBT are needed especially in long-term follow up.